A transcribed enhancer dictates mesendoderm specification in pluripotency. Issue 1 (December 2017) - Alexanian, Michael; Maric, Daniel; Jenkinson, Stephen; Mina, Marco; Friedman, Clayton; Ting, Ching-Chia; Micheletti, Rudi; Plaisance, Isabelle; Nemir, Mohamed; Maison, Damien; Kernen, Jasmin; Pezzuto, Iole; et al.
Abstract Enhancers and long noncoding RNAs (lncRNAs) are key determinants of lineage specification during development. Here, we evaluate remodeling of the enhancer landscape and modulation of the lncRNA transcriptome during mesendoderm specification. We sort mesendodermal progenitors from differentiating embryonic stem cells (ESCs) according toEomes expression, and find that enhancer usage is coordinated with mesendoderm-specific expression of key lineage-determining transcription factors. Many of these enhancers are associated with the expression of lncRNAs. Examination of ESC-specific enhancers interacting in three-dimensional space with mesendoderm-specifying transcription factor loci identifies MesEndoderm Transcriptional Enhancer Organizing Region (Meteor ). Genetic and epigenetic manipulation of theMeteor enhancer reveal its indispensable role during mesendoderm specification and subsequent cardiogenic differentiation via transcription-independent and -dependent mechanisms. Interestingly, Meteor -deleted ESCs are epigenetically redirected towards neuroectodermal lineages. Loci, topologically associating a transcribed enhancer and its cognate protein coding gene, appear to represent therefore a class of genomic elements controlling developmental competence in pluripotency. Long noncoding RNAs (lncRNAs) are key regulators of lineage specification during development. Here, the authors investigate remodeling of enhancers and regulation of the lncRNA transcriptome during mesendoderm specification, and identify a pluripotent stage-specific transcribed enhancer controlling adoption of the mesendodermal cell fate.